PERLINDUNGAN HUKUM TERHADAP UMKM AKIBAT KEBIJAKAN PEMERINTAH DI ERA PANDEMI COVID 19 - Intan Yusmunizar Zahra Daulay (2022)
Since 2020, Indonesia has received threats from outside in the form of a disease, namely a virus with the name COVID-19. By looking at the deteriorating situation, the government last year as a state administrator issued a policy to carry out self-quarantine at home and social distancing, then the Government Policy was regulated under the names PSBB and PPKM to prevent and reduce the rate of spread of this virus. One of the impacts of this policy is in the economic sector, where all economic activities cannot be carried out optimally so that it has an impact on the activities of Micro, Small and Medium Enterprises (MSMEs). The formulation of the problem from this research is, how is legal protection for MSMEs in terms of the MSME Law during the COVID-19 pandemic and how is the government's efforts to protect MSME rights. The research method used is the type of juridical-normative research with a statutory approach with qualitative data analysis techniques. The results of the study show that there is an impact on MSMEs with the issuance of Government Policies in the era of the COVID-19 Pandemic by looking at the declining turnover obtained by MSME actors. The solution that must be carried out by the Government is that regulations regarding legal protection need to be updated and added for MSMEs in the Bandung City Regional Regulation so that this can be implemented in a real and correct manner and MSMEs have strong legal protection and certainty. Keywords: COVID-19, Government Policy, MSMEs.